PSIXOLINGVISTIK TAHLIL: KUNDALIK INGLIZ VA O‘ZBEK NUTQIDA RUHIY HOLAT IFODALARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Language reflects human cognition, particularly in the expression of mental states such as emotions, beliefs, and intentions. This study investigates how English and Uzbek speakers express mental states in everyday speech, analyzing lexical, grammatical, and metaphorical patterns. English favors the direct labeling of mental states through verbs and adjectives, whereas Uzbek relies heavily on descriptive and metaphorical constructions, often involving bodily imagery. Cultural norms and communicative conventions play a significant role in shaping these differences. The findings contribute to cross-linguistic psycholinguistics, intercultural communication, and applied linguistics, providing insights into how cognition and culture influence language.